Tracking the transnational trickster: Gary Shteyngart and his protagonists - Bryla, Martyna Marika (Nordic Association of English Studies, 2018)
The purpose of this paper is to analyze Gary Shteyngart’s protagonists in the light of his works, particularly his debut work, The Russian Debutante’s Handbook (2002) and his memoir, Little Failure (2014). Drawing on the trickster trope and the concept of cultural hybridity, I argue that Shteyngart’s doubly hyphenated characters act as digital-age trickster figures that move between the West and the East with dexterity and ease, exposing persistent mental patterns of othering within multicultural America, but also providing valuable insights into the process of constructing a sense of self on the threshold of several cultural backgrounds.
Keywords: Shteyngart, Gary - Crítica e interpretación; Literatura estadounidense - S. XXI; Gary Shteyngart; East; West; Soviet Union; Trickster; Hybridity; Migrant experience